AB1301 Cardiovascular risk age and vascular age estimations in predicting cardiovascular events in rheumatoid arthritis patients. (12th June 2018) - Wibetoe, G.; Sexton, J.; Ikdahl, E.; Rollefstad, S.; Kitas, G.; van Riel, P.; Gabriel, S.; Kvien, T.K.; Douglas, K.; Sandoo, A.; Arts, E.E.; Wållberg-Jonsson, S.; et al.
Abstract : Background: Rheumatoid arthritis (RA) patients are at high risk of cardiovascular disease (CVD). Risk age estimations are recommended as adjuncts to assessment of absolute 10 year risk of fatal CVD events. Two risk age models based on the Systematic Coronary Risk Evaluation (SCORE) algorithm have been developed; the cardiovascular risk age and the vascular age. Objectives: We aimed to compare the discriminative ability of cardiovascular risk age and vascular age among RA patients and in subgroups of RA patients. Methods: Patients with RA were included from an international consortium, aged 30–70 years at baseline. Those with prior CVD, diabetes and/or users of lipid-lowering and/or antihypertensive therapy at baseline were excluded. Cardiovascular risk age was estimated based on chronologic age, smoking status, total cholesterol and systolic blood pressure at baseline. Vascular age was derived from the 10 year risk of CVD according to the SCORE algorithm, with or without high density lipoprotein cholesterol, using the equations for low and high risk countries. Performance of each risk age model in predicting CVD events was assessed by c-statistics. Results: Among 1867 patients included, 74% were female, median (inter-quartile range) age and disease duration were 52.0 (44.0, 59.9) and 0.6 (0.1, 6.4) years, 72.5% were rheumatoid factor positive, 24.7% were using glucocorticoids and 10.3% were using biologics at baseline. Overall, 144 CVD events occurred. Median follow-up time was 5.0 (2.6, 9.3) years. C-indices across risk models ranged from 0.71 to 0.73 with standard errors of 0.03. Across prediction models, the lowest observed concordance was found among women and in glucocorticoid users and in those with new-onset disease (≤1 year). Additional analyses including RA patients on cardio preventive therapy yielded slightly lower c-indexes. Since SCORE was developed for use in Europe, we performed analyses on European RA patients, which yielded similar results. Certain characteristics were associated with low concordance, but standard errors were high (data not shown). Conclusions: The cardiovascular risk age and vascular age models have comparable performance in predicting CVD in RA patients. The influence of RA disease characteristics on the predictive ability of these prediction models remains inconclusive. Disclosure of Interest: None declared